Screening for geriatric depression in residential care facilities: a systematic narrative review - Azulai, Anna; Walsh, Christine A. (My University, 2015)
Studies in residential care facilities suggest that routine screening can assist in the early detection of geriatric depression. However, the effectiveness of screening instruments in residential care in the US and Canada has not been adequately evaluated. We conducted a systematic narrative review of the English-language literature published between 2000 and 2010 on screening instruments used for depression detection in older adults living in residential care facilities. The review yielded nine scales and their modifications tested in residential care, which we evaluated. We provide specific recommendations for the use of effective scales and discuss implications for practice, policy and research.
Keywords: long-term care; mental health; quality of life; chronic illness; screening